Study of acute toxicity of new thiophene-containing derivatives of 1,2,4-triazole - A. V. Khilkovets; I. M. Bilai (Zaporožskij Medicinskij Žurnal)
Acute toxicity studies are an integral part of preclinical studies of any new biologically active compound. It should be noted that it is this stage of research that is crucial regarding the possibility of further use of a pharmacologically active substance as a drug. This indicator also helps to determine the initial dose for clinical trials and establish a range of potentially safe doses. The data obtained will help determine the direction of new chemical syntheses, replenish the relevant libraries in silico, as well as reveal many other fundamentally important parameters that characterize the interaction in the compound – living organism system.